Chirogenesis in Zinc Porphyrins: Theoretical Evaluation of Electronic Transitions, Controlling Structural Factors and Axial Ligation. Issue 17 (12th July 2021) - Osadchuk, Irina; Aav, Riina; Borovkov, Victor; Clot, Eric
Abstract: In the present work, sixteen different zinc porphyrins (possessing different meso  substituents) with and without a chiral guest were modelled using DFT and TD‐DFT approaches in order to understand the influence of various controlling factors on electronic circular dichroism (ECD) spectra. Two major aspects are influenced by these factors: excitation energy of the electronic transitions and their intensity. In the case of excitation energy, the influence increases in the following order: orientation of the peripheral substituents<substituent's nature<axial ligation. However, the deformation of the porphyrin plane does not affect the excitation energies. In the case of intensity, the influence increases as follows: substituent's nature<conrotatory orientation of the peripheral substituents<deformation of the porphyrin plane<disrotatory orientation of the peripheral substituents<axial ligation. Abstract : Based on DFT and TD‐DFT calculations, it was shown how controlling factors, such as substituent's electron‐donating/withdrawing effect, orientation of the peripheral substituents, deformation of the porphyrin plane, and axial ligation, affect the B electronic transitions and ECD spectra of meso ‐substituted porphyrins.